Forest fragments prioritization based on their connectivity contribution for multiple Atlantic Forest mammals. (February 2022) - Iezzi, M.E.; Di Bitetti, M.S.; Martínez Pardo, J.; Paviolo, A.; Cruz, P.; De Angelo, C.
Abstract: Natural environments worldwide are increasingly restricted to smaller and isolated patches, resulting in major threats to biodiversity. To prioritize conservation efforts, it is important to assess the relative contribution of the habitat remnants to landscape connectivity. We prioritized remnants of Atlantic Forest in Argentina based on their contribution to the connectivity requirements of mammals that are sensitive to landscape transformation by analyzing habitat connectivity and availability for five species with varying habitat requirements and dispersal abilities. We combined graph-based analysis with occupancy models to calculate the resistance matrices and the node attributes, incorporating anthropogenic pressures. Results of connectivity indices were combined for all species so that those that were more sensitive to the loss of connectivity and/or availability had a greater influence on the final prioritization. Five patches had maximum priority for conservation and were vital to maintaining both landscape connectivity and habitat availability. These patches were particularly important for smaller species with low dispersal abilities, for which they constitute suitable habitats. Four percent of the patches were identified as irreplaceable stepping-stones that connected habitat patches for species with intermediate dispersal distances. Patch connectivity was not equally important for all species as they had different dispersal abilities and sensitivity to anthropogenic pressures, which means that the process of territorial planning based on landscape connectivity must include very careful selection of the species involved. With this multi-species model, we generated a spatially explicit tool that proved useful to prioritize forest patches to conserving Atlantic Forest mammals and other fragmented Neotropical forests. Highlights: We developed a multi-species patch prioritization in the Argentinian Atlantic Forest. We created graph-based connectivity models for five sensitive mammal species. We estimated models' inputs using occupancy models to incorporate the effect of poaching. The species contributed differentially to the forest-patch prioritization map. The role of important patches depended on species dispersal abilities.